Folding and Purification of Insoluble (Inclusion Body) Proteins from Escherichia coli. (3rd November 2014) - Wingfield, Paul T.; Palmer, Ira; Liang, Shu‐Mei
Abstract: Heterologous expression of recombinant proteins in E. coli often results in the formation of insoluble and inactive protein aggregates, commonly referred to as inclusion bodies. To obtain the native (i.e., correctly folded) and hence active form of the protein from such aggregates, four steps are usually followed: (1) the cells are lysed, (2) the cell wall and outer membrane components are removed, (3) the aggregates are solubilized (or extracted) with strong protein denaturants, and (4) the solubilized, denatured proteins are folded with concomitant oxidation of reduced cysteine residues into the correct disulfide bonds to obtain the native protein. This unit features three different approaches to the final step of protein folding and purification. In the first, guanidine·HCl is used as the denaturant, after which the solubilized protein is folded (before purification) in an "oxido‐shuffling" buffer system to increase the rate of protein oxidation. In the second, acetic acid is used to solubilize the protein, which is then partially purified by gel filtration before folding; the protein is then folded and oxidized by simple dialysis against water. Thirdly, folding and purification of a fusion protein using metal‐chelate affinity chromatography are described. © 2014 by John Wiley & Sons, Inc.